Science in Agriculture Evaluated at Penn State - George A. VanHorn (Journal of Applied Communications, 1984)
Science in Agriculture, the 30-year-old quarterly magazine of the College of Agriculture at Penn State, was analyzed for reader interest and author satisfaction during the academic year 1980-1981.